2009
DOI: 10.1111/j.1440-1797.2009.01168.x
|View full text |Cite
|
Sign up to set email alerts
|

Late onset Pneumocystis pneumonia in patients receiving rituximab for humoral renal transplant rejection

Abstract: Rituximab has been used increasingly in the treatment of antibody-mediated rejection (AbMR) in solid organ transplantation despite the absence of clinical trials demonstrating efficacy. A contributor to the growing use of rituximab is an apparent lack of morbidity; and there are no reports of specific opportunistic infections associated with its use in renal transplant recipients. Two cases of Pneumocystis pneumonia (PCP) occurring nearly 3 years after administration of rituximab for refractory AbMR are report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 23 publications
1
33
0
Order By: Relevance
“…An additional report described PcP after rituximab therapy in solid transplant recipients receiving this agent for the treatment of humoral allograft rejection. 8 We identifi ed 30 patients with PcP after receiving rituximab, the largest cohort of such patients. The current study holds several important advantages over prior studies.…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…An additional report described PcP after rituximab therapy in solid transplant recipients receiving this agent for the treatment of humoral allograft rejection. 8 We identifi ed 30 patients with PcP after receiving rituximab, the largest cohort of such patients. The current study holds several important advantages over prior studies.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…2 In addition, recent stud ies have suggested that the novel anti-B-lymphocyte agent rituximab may be associated with the development of PcP. [3][4][5][6][7][8][9][10][11] Rituximab is a monoclonal antibody that binds to the CD20 antigen on B lymphocytes. It has been used for both hematologic malignancies such as chronic lymphocytic leukemia and for non-Hodgkin's lymphoma.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However 2 cases of late onset PCP have also been described in where B cells counts at the time of PCP diagnosis were still low -respectively 0.01 and 0.05 x10^9/L -nearly 3 years after the administration of a single dose of RTX (500 mg) for humoral rejection [28].…”
Section: Discussionmentioning
confidence: 99%
“…Although the rate of infection was similarly high in both groups (45.5% rituximab-treated vs. 53.9% controls), the mortality rate was significantly higher in the rituximab group (9.1% vs. 1.6%). 27 Other reports have documented cases of late-onset Pneumocystis jiroveci pneumonia, 28 cryptogenic organizing pneumonia 29 and JC virus associated PML 30 in patients treated with rituximab in post-transplant period. These potential complications show that the particular indications for rituximab usage must be further elucidated through larger-scale randomized trials that compare rituximab with conventional therapies.…”
Section: Ischemia and Reperfusion Injury Preventionmentioning
confidence: 99%